Puchong Financial Corporate Center Tower 4 Puchong Selangor Darul Ehsan / Eddie Firdaus Farid ... [et al.] - Farid, Eddie Firdaus; Mohd Ali, Ida Shuhada; Md Yazlli, Mohamad As’ad; Abu Bakar, Mohd Shahrulnizam (Universiti Teknologi Mara, Perak, 2016)
Puchong Financial Corporate Center one of the company under IOI Properties Group but Flora Development is managing this company. There are many other companies under IOIPG such as, Legend Advance SDN BHD, Commercial Wing SDN BHD, Multi Wealth Singapore PTD ltd and Future Link Properties PTE ltd.All the company under IOI is different usage and function. IOI Properties Group Berhad is one of Malaysian public listed property developers. It has built a solid reputation as the esteemed property arm of IOI Group prior to its successful onto the Main Board of Malaysian Stock Exchange on 15 January 2014. Today, IOIPG is renowned as one of the largest property companies in the country with a proven track record spanning more than three decades in the property development industry. Its principal activities include property development, property investment, leisure and hospitality. It has successfully developed sustainable townships in sought-after regions of Klang Valley and Johor in Malaysia while embarking on property developments in Singapore and the People‟s Republic of China. IOIPG currently has a total of 10,000 acres of land bank in Malaysia and abroad.